Corporate Governance and Earnings Management：Evidence from China - Liu, Ying (2020)
Earnings management is an essential field of modern accounting research. Earnings management is a choice of company's financial accounting policy. Earnings management behaviour may distort accounting information, which is harmful to the stable development of the companies in the future. Therefore, in the accounting field, how to control the phenomenon of earnings management is one of the hot issues in recent years. In order to reflect the level of earnings management of Chinese listed companies, this article uses the modified Jones model to estimate the absolute value of manipulated accrued profits. Data on Shanghai and Shenzhen Stock Exchanges from 2015 to 2019 of listed companies are used to carry out a data analysis about the correlation between corporate governance and earnings management. Based on the analysis, relevant suggestions are proposed about how to design the corporate governance mechanism and decrease the phenomenon of earnings management.